Representations and Stereotypes of disabled people as consumers: the drama of characters with disabilities in Brazilian telenovelas - Faria, Marina Dias de; Casotti, Leticia Moreira (Organizações & Sociedade, 2014)
Despite being important mass media of the culture, the values and the perspectives existing in a society, cultural texts shape possibilities unexplored in research on consumer with disabilities. In Brazil, soap operas seem to be cultural texts suitable for such studies in view of the importance given by the soap operas as a program for all classes. Defined as the study aimed to discussrepresentations and stereotypes of disabled people as consumers presented in Brazilians telenovelas . To achieve the objective 22 scenes of Brazilian soap operas which show characters with disabilities in situations of consumption were analyzed. The study results highlight the need for companies, public institutions and society in general review the way they deal with these almost invisible to consumers often are not considered as potential customers and are excluded from public policy actions.